The Effectiveness of Canva as an Instructional Tool in Improving Students’ Academic Performance: A Meta-Analysis - Astaño, Jereme (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study evaluated the effectiveness of Canva in improving students’ academic performance. The present inquiry employed a meta-analysis method using various publications retrieved from DOAJ, ERIC, Dimensions, and Google Scholar. A total of 22 studies with 26 valid datasets (n = 1540) were analyzed, records were primarily from Indonesia and published from 2022 to 2024. Most documents were considered to be of moderate quality, with concerns or potential risks related to the domains on the comparability of the comparison group and blinding of assessment. Results showed that Canva has a very large and significant effect (g = 1.703, p < .001) on students’ academic performance, though substantial heterogeneity and publication bias were detected. Sensitivity analyses, such as the Trim-and-Fill and the WAAP method, confirmed the robustness of the findings. The results also revealed that country and subject influenced the effect size, but uneven subgroup distribution limited conclusive findings. Conversely, duration, class size, grade level, assessment blinding, and academic outcome, showed no significant moderating effects. Noteworthy, subgroup analysis suggests that Canva has a potential and greater effect in Indonesia, particularly in English subjects, with smaller class sizes, among high school and university students who actively engage in the platform to improve communication skills. This meta-analysis provides empirical evidence of the positive effect of Canva on students’ academic performance. Lastly, this investigation offers practical recommendations for future studies and practices.